Analisis Pengendalian Intern Atas Persediaan Barang Dagang Pada PT XYZ - Anggun, Victoria; Paranoan, Natalia; Sanda Sipi, Afian Dezi (Universitas Multi Data Palembang, 2025)
The more technology develops in the business world, the more competition in the business world increases. Problems regarding inventory such as excess or lack of stock. Therefore, the company must have good internal control to minimize the risk of major losses for the company. Because there are quite a lot of types of products and mobility of goods in and out, the problem that is feared will occur is the physical difference between the inventory in the warehouse and the amount recorded in the inventory book, loss or theft of stock. This study uses a qualitative descriptive method. Overall, PT Anugerah Karya has not fully implemented the five components of COSO. There are still a number of fundamental problems that need to be addressed. The results of this study indicate that internal control at PT Anugerah Karya Magantha is less effective with the internal inventory control standards according to COSO